PENGARUH KOMUNIKASI INTERPERSONAL PIMPINAN DAN MOTIVASI KERJA TERHADAP LOYALITAS KERJA KARYAWAN KEMBAR CAFE KOTA MEDAN - Aulia Fathurrahman; Elfi Yanti Ritonga (Universitas Negeri Yogyakarta, 2026)
on employee job loyalty at Kembar Cafe, Medan. A quantitative research approach was employed, with leaders’ interpersonal communication and work motivation serving as the independent variables, while employee job loyalty functioned as the dependent variable. Data were collected through an online questionnaire distributed via Google Forms using a modified Likert scale without a neutral response option. The population of this study consisted of 65 employees of Kembar Cafe, and a sample of 40 respondents was determined using the Slovin formula with a 10% margin of error. Instrument validity and reliability tests were conducted to ensure the accuracy and consistency of the measurement tools. Data were analyzed using Pearson’s Product-Moment correlation and multiple linear regression analysis with the assistance of SPSS software. The findings reveal that leaders’ interpersonal communication and work motivation have a positive and significant effect on employee job loyalty, both partially and simultaneously. These results indicate that improvements in the quality of interpersonal communication between leaders and employees, as well as increased levels of work motivation, contribute to higher levels of employee job loyalty.